Selected papers from the 7th International Symposium on Electric and Magnetic Fields, June 2006 - Dular, Patrick; Meunier, Gerard; Piriou, Francis (Compel ;, 2008)
The purpose of the EMF Symposium is to throw a bridge between the recent advances of research in numerical modeling of electromagnetic fields and the growing number of industrial problems requiring such techniques. Therefore, beside classical sessions on the progress of computational methods, special sessions were devoted to advanced industrial applications of electromagnetic modeling. The topics included numerical methods and techniques, coupled problems (mechanical, thermal, electric circuits), material modeling, optimization and specific application oriented numerical problems.